SIMULATION OF TRANSPORT PHENOMENA IN InP (Sciences & Technology. A, exactes sciences, 2004)
In the present work we report results of the simulation of transport phenomena in InP under uniformelectric fields in both transient and steady state regimes using semi-classical Ensemble Monte Carlomethod (EMC). The EMC algorithm used consists mainly of the simulation of an ensemble of carriersand follows their history in parallel for a sequences of very short time intervals in three dimensionalmomentum and real spaces. After each sampling interval, data (drift velocity, energy…) is collected foreach particle and the values are averaged. In our simulation an ensemble of 105 electrons are used. Theprogram was written with Fortran 90 language and run on IBM PC(PIII, 800GHz). The obtained resultsare in good agreement with reported experimental data.